The National Curricular Guidelineand the Continuing formation of Science teachers:collaborative learning for pedagogical use of the non formal educational settings - Celcino Neves Moura; Tadeu Davel Monghol; Maria da Penha Kapitzky Dias; Carlos Roberto Pires Campos (Universidade Estadual de Alagoas, 2020)
This article aims to approach about a teacher's formation in which Interdisciplinary teaching practices were developedaccording to the bases ofthe National Curriculum Guidelines of Brazil, in order toproducea criticaldialogue between the formal and non-formal educational settings, especially in the context of science education. This study adopted the qualitative research approach, and the case study design was used. The qualitative research paradigm was appropriate because there was an educational problem tobe discussed which demanded to be understood in its details.Data was collected by the use of logbooksand interviews and their contents approached from the Bardin's (2011) perspective.The formation wasconducted with 15 teacher-students in Marataízes city, southern coast of Espírito Santo State, Brazil. Results revealed the non formal educational settings potentiality on approachinginterdisciplinary content ofgeosciences and natural sciences, besides, wealso discussed aspects of the history, culture, human rights, social and environmental.For many, that was for the first experience in field classes and in direct contact with nature.